2018
DOI: 10.1111/cxo.12689
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of refractive errors in children in India: a systematic review

Abstract: Uncorrected refractive error is an avoidable cause of visual impairment which affects children in India. The objective of this review is to estimate the prevalence of refractive errors in children ≤ 15 years of age. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines were followed in this review. A detailed literature search was performed to include all population and school-based studies published from India between January 1990 and January 2017, using the Cochrane Library, Medli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
54
3
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(64 citation statements)
references
References 34 publications
(33 reference statements)
6
54
3
1
Order By: Relevance
“…Authors referred to the cut off points as recommended by Sheeladevi et al to consider a refractive error significant (myopia of ≥-0.75D, hypermetropia of more than +2D, astigmatism cylindrical error of more than 0.75D). 11 In thin study, 503 (53.2%) children were males and 443 (46.8%) were females. The prevalence of refractive errors was found to be slightly higher in males, though the difference was not statistically significant.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Authors referred to the cut off points as recommended by Sheeladevi et al to consider a refractive error significant (myopia of ≥-0.75D, hypermetropia of more than +2D, astigmatism cylindrical error of more than 0.75D). 11 In thin study, 503 (53.2%) children were males and 443 (46.8%) were females. The prevalence of refractive errors was found to be slightly higher in males, though the difference was not statistically significant.…”
Section: Discussionmentioning
confidence: 85%
“…Being a hospital-based study, this study had a greater number of children with refractive errors within the given study period (i.e, 946 as compared to 898 highest among the population-based studies and 582 highest among the school-based studies). 11 Dandona et al screened 1726 patients but they had included patients till 99 years of age in their study and Saxena et al included 1,297 patients but their aim was to find the prevalence of myopia in a group of population. 8,9 Authors used a logMAR digital vision chart to assess the vision and every child in this study underwent dilated retinoscopy to confirm the refractive error.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 In a study conducted by Sheeladevi et al, the prevalence of defective vision was higher among girls than boys. 18 In a study conducted by Shrestha, the association between ocular morbidity, age and sex. 8 P value was considered significant at 0.05 for 95% confidence interval.…”
Section: Discussionmentioning
confidence: 99%
“…According to a 31% 46% 23% 3 to 8 years 9 to 12 years 13 to 17 years systematic review conducted on the studies in India on refractive errors in children, the overall prevalence was found to be 8%. 10 The present study is hospital-based study, hence the likelihood of patients having refractive error is high as they are already screened and referred from schools or are having ocular complains.…”
Section: Prevalence Of Refractive Errormentioning
confidence: 99%